Extending the application of integral frame abutment bridges in earthquake‐prone areas by using novel isolators of recycled materials. (25th May 2016) - Mitoulis, Stergios A.; Palaiochorinou, Anastasia; Georgiadis, Ilias; Argyroudis, Sotiris
Summary: Integral abutment bridges (IABs) are jointless structures without bearings or expansion joints which require minimum or zero maintenance. The barrier to the application of long‐span integral abutment bridges is the interaction of the abutment with the backfill soil during the thermal expansion and contraction of the bridge deck, that is, serviceability, or when the bridge is subjected to dynamic loads, such as earthquakes. The interaction of the bridge with the backfill leads to settlements and ratcheting of the soil behind the abutment and, as a result, the soil pressures acting on the abutment build up in the long term. This paper provides a solution for the aforementioned challenges by introducing a novel isolator that is a compressible inclusion of reused tyre‐derived aggregates placed between the bridge abutment and the backfill. The compressibility of typical tyre‐derived aggregates was measured by laboratory tests, and the compressible inclusion was designed accordingly. The compressible inclusion was then applied to a typical integral frame abutment model, which was subjected to static and dynamic loads representing in‐service and seismic loads correspondingly. The response of both the conventional and the isolated abutment was assessed based on the settlements of the backfill, the soil pressures and the actions of the abutment. The study of the isolated abutment showed that the achieved decoupling of the abutment from the backfill soil results in significant reductions of the settlements of the backfill and of the pressures acting on the abutment. Hence, the proposed research enables extending the length limits of integral frame bridges subjected to earthquake excitations. Copyright © 2016 John Wiley & Sons, Ltd.